Anti-TNF-αα therapy for ankylosing spondylitis. Issue 5 (October 2007) - Frech, Tracy
Management of the inflammatory symptoms of ankylosing spondylitis has been revolutionized by use of TNF inhibitors. Although three TNF inhibitors have been approved by the US FDA, none has proven to be superior for treatment of ankylosing spondylitis. Our knowledge of TNF and its receptors suggests that there should be differences in the mechanism of the inhibitors. In addition to long-term safety data and structural modification information, knowledge of the effect of TNF inhibition on extra-articular manifestations of the disease is needed.